PENGARUH KONFLIK KERJA TERHADAP SEMANGAT KERJA KARYAWAN DI PT. PARAMITA BANGUN SARANA - Toto Widiarto; Agus Jamaludin; Feri Feri (JABE (Journal of Applied Business and Economic), 2016)
This study reveal human capital is one of company resources that have value and role in the use of others. Therefore, a proper  management system is important and required to determine the success of company. A good company must be supported with high qualified employees that have invitiative, creative and discipline. To have this attributes, a qualified leader plays an important role in supporting professional development of its subordinate. They matter for the extent to which the center support, stimulates and subsidies professional development. Therefore, staff quality is maintained by leadership that  motivates and encourage working as team, information sharing and professional staff development. The purpose of this research is to investigate the impact of work conflict with work motivation at PT. Paramita Bangun Sarana. The sample is collected based on survey to 100 employess. The methods are validitas test, reliability test, simple regression,  correlation test, coefficient determination,  and hypothesis. Based on the sample calculation and analyze, we come into regression equation:  ?               With this simple method, the conlusion is that the variabel of work conflict has significant impact to work motivation. With value of                                     and coefficient determinate  (KD)=47,61% with result of correlation coefficient r=0,69. Therefore, we conclude that work conflict influences work motivation of employee (hypothesis is accepted).